2019
DOI: 10.1002/ecs2.2982
|View full text |Cite
|
Sign up to set email alerts
|

Female Greater Prairie‐Chicken response to energy development and rangeland management

Abstract: Wildlife habitat use is the result of behaviors that occur at multiple spatial and temporal scales. The interactions between these behaviors can often result in complex patterns of selection that can make it challenging to select the most appropriate scale to implement management actions. Greater Prairie‐Chickens (Tympanuchus cupido), a declining grassland grouse species, face many conservation challenges throughout its distribution, including increased fragmentation from anthropogenic activities (e.g., energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 61 publications
(142 reference statements)
1
12
0
Order By: Relevance
“…In addition to the anthropogenic development variables (described in next paragraph), we used a consistent base model for all iSSA models that included variables that we expected to have influenced prairie‐chicken movement and selection decisions independent of development (Table 1). We selected environmental and habitat variables based on previous publications describing prairie‐chicken habitat selection (Londe et al, 2019; Winder et al, 2015), and we selected movement variables based on recommendations from Avgar et al (2016). For the habitat and environmental variables in the base model we included distance to woodlands and lek site, as prairie‐chickens have been shown to consistently avoid trees throughout their entire annual cycle while generally remaining close to the location of the lek where they were captured (Londe et al, 2019; Winder et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to the anthropogenic development variables (described in next paragraph), we used a consistent base model for all iSSA models that included variables that we expected to have influenced prairie‐chicken movement and selection decisions independent of development (Table 1). We selected environmental and habitat variables based on previous publications describing prairie‐chicken habitat selection (Londe et al, 2019; Winder et al, 2015), and we selected movement variables based on recommendations from Avgar et al (2016). For the habitat and environmental variables in the base model we included distance to woodlands and lek site, as prairie‐chickens have been shown to consistently avoid trees throughout their entire annual cycle while generally remaining close to the location of the lek where they were captured (Londe et al, 2019; Winder et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…We defined the post-nesting season as the period after a female concluded nesting activity for the year (typically late May to early June) until 14 September when the last broods are likely to have broken up, prior to the fall/winter season. The start of the post-nesting period was determined separately for each individual based on when individual females were observed leaving the nest site (Londe et al, 2019). This period corresponds to the time when females are either raising newly hatched chicks or are recovering from previous reproductive efforts.…”
Section: Prairie-chicken Capture and Monitoringmentioning
confidence: 99%
See 2 more Smart Citations
“…Nest site selection.-We calculated the number of nests that occurred in each time since fire category to provide a course index of habitat selection during our study. Additional details about nest site selection at our study site can be found in Hovick et al (2014Hovick et al ( , 2015 and Londe et al (2019).…”
Section: Discussionmentioning
confidence: 99%